2012
DOI: 10.4028/www.scientific.net/amr.569.395
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Study on High-Temperature Ventilated Cavitating Flow Considering the Compressibility of Gases

Abstract: A numerical simulation approach of ventilated cavity considering the compressibility of gases is established in this paper, introducing the gas state equation into the calculation of ventilated supercavitating flow. Based on the comparison of computing results and experimental data, we analyzes the differences between ventilated cavitating flow fields with and without considered the compressibility of gases. The effect of ventilation on the ventilated supercavitating flow field structure is discussed consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Spurk (2004) extended the gas loss theory of ventilated cavities under isothermal conditions to nonisothermal conditions through a theoretical derivation. Zhao et al (2012) further explored the influence of temperature through a numerical method, and found that an increase in the ventilation temperature caused the cavity to become flat and the resistance to decrease, although the fluctuation range was larger than at low temperatures. Lv et al (2021) and Ma et al (2019) explored the unsteady behaviour of ventilated cavities below axisymmetric bodies through numerical approaches, and found that the re-entrant jet was closely related to the unsteady behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Spurk (2004) extended the gas loss theory of ventilated cavities under isothermal conditions to nonisothermal conditions through a theoretical derivation. Zhao et al (2012) further explored the influence of temperature through a numerical method, and found that an increase in the ventilation temperature caused the cavity to become flat and the resistance to decrease, although the fluctuation range was larger than at low temperatures. Lv et al (2021) and Ma et al (2019) explored the unsteady behaviour of ventilated cavities below axisymmetric bodies through numerical approaches, and found that the re-entrant jet was closely related to the unsteady behaviour.…”
Section: Introductionmentioning
confidence: 99%